2020
DOI: 10.1007/s00415-020-09724-4
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic inclusion body myositis: no specific cardiac involvement in cardiac magnetic resonance tomography

Abstract: Objective To investigate cardiac involvement in patients with sporadic inclusion body myositis (IBM) by cardiac magnetic resonance tomography (CMR). Methods A case series of 20 patients with IBM underwent basic cardiac assessment and CMR including functional imaging, native and contrast-enhanced T1-weighted, and late gadolinium enhancement (LGE) imaging. Results All IBM patients reported no cardiac symptoms. Echocardiography was normal in 16/17 IBM patients. In CMR, IBM patients had normal ejection fractions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a recent study by Key Words: biopsy ◼ gadolinium ◼ myocardium ◼ myositis, inclusion body ◼ troponin T Rosenbohm et al, 35% of patients with IBM reportedly had LGE on CMR. 2 Although the authors concluded that it was a nonspecific finding in the case series, we speculate that it is subclinical cardiac involvement associated with IBM. Imaging shows LGE is most common in the inferior and inferolateral segments, which is similar to the findings of cardiac involvement in dermatomyositis and polymyositis.…”
Section: Multiparametric Cardiac Magnetic Resonance Imaging Of Cardia...mentioning
confidence: 60%
“…In a recent study by Key Words: biopsy ◼ gadolinium ◼ myocardium ◼ myositis, inclusion body ◼ troponin T Rosenbohm et al, 35% of patients with IBM reportedly had LGE on CMR. 2 Although the authors concluded that it was a nonspecific finding in the case series, we speculate that it is subclinical cardiac involvement associated with IBM. Imaging shows LGE is most common in the inferior and inferolateral segments, which is similar to the findings of cardiac involvement in dermatomyositis and polymyositis.…”
Section: Multiparametric Cardiac Magnetic Resonance Imaging Of Cardia...mentioning
confidence: 60%
“…In this study, the rate of atrial fibrillation, sub-endocardial infarction, and strokes were higher in IBM patients. While higher frequency of hypertension, hyperlipidaemia, myocardial infarction, and congestive heart failure in IBM patients was reported in a single study, focused studies did not find any definitive cardiac involvement in IBM patients (33,34). On the other hand, higher rates of atrial fibrillation in patients with IIM compared to patients with other autoimmune diseases has been reported (35,36).…”
Section: Discussionmentioning
confidence: 93%
“…However, these changes were attributed to hypertensive heart disease in these patients. Of note, there was no statistical difference in the LGE between patients and controls [ 104 ].…”
Section: Methodsmentioning
confidence: 99%